Hi , Im Confused And Need Help Solving This Equation x+6=-x-2
How To Solve ?
The best way is to get all of your variables on one side, and all of the numbers on the other.
So we have:
x + 6 = -x -2, lets start by bringing all of the x's to one side (i.e to the left)
x + 6 - (-X) = -2, which simplifies to 2x + 6 = -2.
Next, lets get all the other numbers on the other side.
2x = -2 - 6, which simplifies to 2x = -8...
Final step, divide both sides by 2...and we have x = -4 as your final answer.
Hope that helps.